2000
DOI: 10.1086/315309
|View full text |Cite
|
Sign up to set email alerts
|

An Isogenic Hemoglobin Receptor–Deficient Mutant ofHaemophilus ducreyiIs Attenuated in the Human Model of Experimental Infection

Abstract: Haemophilus ducreyi expresses a conserved hemoglobin-binding outer-membrane protein (HgbA). To test the role of HgbA in pathogenesis, we infected 9 adults with isolate 35000 and its isogenic hgbA-inactivated mutant (FX504) on their upper arms in a double-blinded, escalating dose-response study. Papules developed at similar rates at sites inoculated with the mutant or parent. The pustule-formation rate was 55% (95% confidence interval [CI], 30. 8%-78.5%) at parent sites and 0 (95% CI, 0-10.5%) at mutant sites (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 37 publications
(73 reference statements)
1
73
1
Order By: Relevance
“…A modified escalating doseresponse study was used to compare the virulence of 35000HP-SMS2 and 35000HP (1,21,36). In the first iteration, we attempted to inoculate three subjects at three sites with EDDs of The result of the first iteration suggested that the mutant formed pustules at a rate similar to that of the parent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A modified escalating doseresponse study was used to compare the virulence of 35000HP-SMS2 and 35000HP (1,21,36). In the first iteration, we attempted to inoculate three subjects at three sites with EDDs of The result of the first iteration suggested that the mutant formed pustules at a rate similar to that of the parent.…”
Section: Resultsmentioning
confidence: 99%
“…H. ducreyi clumps in vitro, and it would be technically difficult to perform a mutant-parent comparison using a single dose of bacteria. Therefore, we evaluated the virulence of the mutant using a modified escalating dose-response study, as described previously (1,21,36). Within an EDD range of 17 to 120 CFU, where the parent generally forms pustules (2), the parent strain formed pustules at 70% of sites and the mutant formed pustules at 40% of sites (P ϭ 0.14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the expression of HmbR in vivo has not been unambiguously confirmed, the expression of other hemoglobin receptors in vivo, such as those of certain Haemophilus species, has been reported. The in vivo expression of the outer membrane hemoglobin receptors in H. influenzae has been demonstrated in the human model for acute otitis media, and the hemoglobin receptor for Haemophilus ducreyi has been shown to be essential for infection in a human model system (6,172). A strong disadvantage associated with both HmbR and HpuAB as vaccine candidates is the phase variation of their expression and sometimes a very high frequency of switching to "off."…”
Section: Downloaded Frommentioning
confidence: 99%
“…The ability of H. ducreyi to obtain heme from hemoglobin is required for pustule formation. An isogenic hgbA mutant which is unable to utilize hemoglobin was unable to form pustules in a human experimental model of infection (5). As HgbA is conserved in geographically diverse isolates, we developed an IC test based on these MAbs to this protein.…”
mentioning
confidence: 99%